Teacher’s professional values (objectivity, honesty, integrity and self-control): Validating the mediating role of ethnical perception using confirmatory factor analysis (CFA) - Ntumi, Simon; Bulala, Tapela; Yeoboah, Abraham; Gyapong Nimo, Daniel; Serwaa Antwi, Esther (Open Science Journal, 2024)
Aim: The study aim was to validate how ethical perception could mediate teachers’ professional values such as objectivity, honesty, integrity and self-control in the Ghanaian context using CFA. Methods: A cross-sectional study design was employed and the convenience sampling technique was used to administer a total of 248 questionnaires to basic and senior high school teachers in the southern part of Ghana. Findings: The study found that objectivity as one of the professional values of teachers has negative effect on the ethical perceptions of teachers and the results were not statistically significant (β=-0.015, SE.=0.061, p=0.800**, n=248). It was again found that integrity was statistically significant and had negative effect on ethical perceptions of teachers (β =-0.131, SE.=0.079, p<0.01, n=248). Again, it was found that honesty has statistically significant a positive effect on the ethical perceptions of teachers (β =0.413, SE.=0.066**, p<0.001, n=248). It was again found that self-control was statistically not significant and had negative effect on ethical perceptions of teachers (β =-0.097, SE.=0.096, p=0.309**, p<0.001, n=248). Finally, it was found that ethical perception was statistically significant and had positive effect on the ethical decisions of teachers (β =0.427, SE.=0.065, p<0.001, n=248). In the end, the results suggest that there is a partial mediation effect of professional values on teachers’ ethical decisions (Obj.=-.007; p=.853; Hon.=.176; p=.003**; p=.039*; Inter.=-.056; Self-Con.=-042; p=.234**, p<0.001, n=248). Conclusion: The study concluded that professional values, ethical perceptions and decisions of ethical behavior of teachers are an important part of a good workplace culture and should be encouraged in order to foster a strong working relationship for effective teaching and learning process. Recommendation: The study recommended that school heads in Ghana should create a framework at the workplace in which teachers can test and practice their professional values, ethical perceptions and decisions of ethical behavior with others to promote effective teaching and learning.